Desarrollo: viejos mitos y nuevos paradigmas - Montobbio, Manuel (Revista Española de Desarrollo y Cooperación, 2023)
This article goes over the main paradigms regarding development. It will start with the primitive conception of development, based on unilateralism and a strong economic perspective, to end with an holistic, human and not transitive meaning of the concept.